2004
DOI: 10.1111/j.1399-3038.2004.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary prevention of allergic diseases in infants and small children

Abstract: The role of primary prevention of allergic diseases has been a matter of debate for the last 40 years. In order to shed some light on this issue, a group of experts of the Section of Pediatrics EAACI reviewed critically the existing literature on the subject. An analysis of published peer-reviewed observational and interventional studies was performed following the statements of evidence as defined by WHO. The results of the analysis indicate that breastfeeding is highly recommended for all infants irrespectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
3
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(181 citation statements)
references
References 93 publications
(110 reference statements)
1
169
3
8
Order By: Relevance
“…The study has been criticized for retrospective determination of breastfeeding and unclear definitions of atopic heredity. 22 There was also no evidence of a "dose-response" effect of breastfeeding on the incidence of atopy or asthma.…”
Section: Asthmamentioning
confidence: 91%
See 4 more Smart Citations
“…The study has been criticized for retrospective determination of breastfeeding and unclear definitions of atopic heredity. 22 There was also no evidence of a "dose-response" effect of breastfeeding on the incidence of atopy or asthma.…”
Section: Asthmamentioning
confidence: 91%
“…21 Consideration of a large number of studies on maternal diet, not all of which were randomized or included dietary restriction during lactation, demonstrated no impact on various outcomes among the majority of the studies, particularly when follow-up was beyond 4 years, and led one recent group of reviewers to conclude that there is no convincing evidence for a long-term preventive effect of maternal diet during lactation on atopic disease in childhood. 22 A 2006 Cochrane review also concluded that there was insufficient evidence that antigen avoidance during lactation was beneficial in preventing atopic disease in the breastfed infant, with the exception of atopic dermatitis. 5 Because the available published trials have had methodologic shortcomings, more data are necessary to conclude that the avoidance of antigens during lactation prevents atopic dermatitis in infants.…”
Section: Dietary Restrictions For Pregnant and Lactating Womenmentioning
confidence: 99%
See 3 more Smart Citations